INSOLATION-CONTROL ON THE LATE CRETACEOUS HYDROLOGICAL CYCLE AND TROPICAL AFRICAN CLIMATE-GLOBAL CLIMATE MODELLING LINKED TO MARINE CLIMATE RECORDS - Floegel S.; Wagner T. (My University, 2006)
Data from Late Cretaceous paleoclimate simulations and their linkage to a geological model derived from long-term high-resolution proxy-data indicate and support strong relationships between African climate and tropical Atlantic sedimentation. Here, we present results from an interdisciplinary study. By varying only one parameter in the set of orbital boundary conditions of the numeric model, we focus on the climatic impact of precessional forcing on the global and regional climate system. As a result, new insights to the internal dynamics of climate, the different compartments and fluxes of the hydrological cycle, and finally the sedimentary response within the oceanic realm during greenhouse conditions have been approached. The climate models suggest that insolation changes at 25-55°S are the trigger for cyclic variations of the tropical hydrological cycle of northern Africa. Between the various models, a maximum difference in insolation at the top of the atmosphere of 14 W/m2 is needed to produce the documented changes in the hydrological cycle. First of all, the simulations do not suggest any substantial latitudinal movement of the ITCZ over the course of one precessional cycle. The models rather indicate cross-latitudinal variation of pressure systems and variation in the magnitude and direction of surface winds, linking tropical Africa to the mid-southern latitudes. This cross-latitudinal atmospheric teleconnection denotes a reduced role of the tropics as driver of Cretaceous climate system. Therefore, the linkage of proxy-based geological and numeric models rather supports the idea that tropical Atlantic black shale formation in the Late Cretaceous was ultimately triggered by climate change in mid-southern latitudes, with precipitation and river discharge being the transport mechanisms. As a hypothesis that will be tested in the near future, we speculate that the mid-latitudes represent the "ultimate" region of climate signal formation during times of extreme global warmth. © 2005 Elsevier B.V. All rights reserved.
Keywords: BLACK SHALE FORMATION; CRETACEOUS; HYDROLOGICAL CYCLE; LATITUDINAL ATMOSPHERIC CONNECTION; MARINE GEOCHEMICAL SIGNAL FORMATION; PALEOCLIMATE; Mesozoic::Cretaceous; Мезозой::Меловая